Analisis Keputusan Pendanaan Bagi Usaha Kecil Kerajinan Melalui Lingkungan Eksternal dan Kapasitas Manajerial di Nusa Tenggara Barat - Amin, Nur Asikin (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2015)
Abstract:Â Craft small business in Western Lesser Sundas, still faced a various of obstacles, such as: The minimum obstacle of the managerial capacity of craft small entrepreneurs in term of the weakness of business planning, organization, management, and control; The external obstacles in term of still less attention of government in the cultivation and development of business, supporting means and infrastructure that still limited, and the involvements of big enterprises and social institutions in the cultivation that not yet optimal.. The research population was the entire small business crafters in 10 Regencies/Towns in Western Lesser Sundas Province who continually did production activities amounted to 3,719 crafters. It was by using the Generalized Least Square Estimation (GLSE), structural equation model (SEM) analysis, and proportional random sampling method on 361 crafter respondents. The research result indicated that: 1) External environment had effect on the managerial capacity of craft small business; 2) External environment had effect on the funding decision of craft small business; 3) Managerial capacity had effect on the funding decision of craft small business in Western Lesser Sundas Province. Key words: external environment, managerial capacity, funding decision.